Bioaccumulation of hexavalent chromium in commercially edible fish grass carp, Ctenopharyngodon idella - Aslam, Sonia; Muhammad Yousafzai, Ali; Javed, Aleena (Penerbit Universiti Kebangsaan Malaysia, 2022)
The current research was conducted with the aim to investigate the rate of chromium accumulation in various tissues of commercially valuable freshwater fish, Grass Carp, Ctenopharyngodon idella. Investigation included various tissues of skin, muscles, liver, swim bladder, intestine, and gills in fish. For this purpose, the fish were exposed to sub lethal concentration of hexavalent chromium in the form of potassium dichromate with a dose of 120 mg/L for 40, 20 days and 10 mg/L for 7, 25, 40 and 60 days. Forty fish of the same weight and length (70.45±2.91 g and 7.32±0.16 inches) were used in the present research. Chromium was estimated after acid digestion of the sample tissues and further analyzed through atomic absorption spectrophotometer (Spectra AA6300 China). The results showed that in all the experiments intestine remained the highly accumulative tissue and the accumulation of chromium in the intestine increased with the increase in exposure time i.e., 0.63±0.21 after 7 days, 0.83±0.35 after 25 and 1.63±0.44 after 60 days. Finding of this research work supports that the route of metal uptake was mainly oral instead of absorption by gills or skin.